Greener products : the making and marketing of sustainable brands - Iannuzzi, Al (CRC Press, 2024)
"Sustainability and its competitive advantage is the goal of every company and any brand that wants to stay successful in the marketplace. Customers also gravitate to brands that manage sustainability issues well. Greener Products: The Making & Marketing of Sustainable Brands, written by a renowned sustainability expert, continues to address the latest developments in the extremely fast-moving field of sustainability. Thoroughly updated, this third edition introduces new case studies, includes a new chapter on natural capital cost accounting, and explores the best practices of leading global companies and helps readers learn what it is that makes them successful"-- Provided by publisher.
First edition published by CRC Press 2012.
Keywords: Green marketing.; Green products.; elektronické knihy; electronic books